PERAN PEREMPUAN DALAM USAHA PEMBUATAN TEMPE DI DESA LAMBUSA KECAMATAN KONDA KABUPATEN KONAWE SELATAN - Rifka Taufika; Hartina Batoa; Suriana Suriana (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2023)
The low level of household income encourages all elements to be utilized as much as possible to improve the household economy, including housewives. This study aims to examine the role of women in the tempe-making business in Lambusa village, Konda subdistrict, South Konawe Regency. The population in the study were all women who were active in Mr. Madarin's tempe making business in Lambusa Village. The informants in the study were divided into two groups, namely the main informants (female employees working in the tempe business) and the supporting informants (tempe business owners). The determination of the informants was purposive with the criteria that the informants were considered to have the capacity related to the role of women as business actors who were able to provide information related to the tempe-making business, so the research informants were 6 people. The research data were collected through survey, interview, documentation and recording methods using an instrument in the form of an interview guide. The descriptive qualitative analysis used in this research consists of three stages, namely data reduction, data presentation, and conclusion or data verification. The results showed that the role of women in the business activities of tempeh production included preparation of tools and materials, washing, boiling, skinning soybeans, soaking, steaming, leavening, and packaging. The role of women is included in the active role category because women are always active in each stage of the tempeh production process. Although the main role of women is basically only in the wrapping or packaging process.